Early response of soils to violent disturbances - Kharab, Abdelwahab; Benbourenane, Jamal (International Journal of Applied Mathematical Research, 2017)
A one-dimensional model dealing with underground explosions as experienced in areas such as mining or excavations is presented. When an explosion in a typical soil medium occurs, soil material is displaced and shock waves propagate in the soil medium. Soil is considered as a floating, ideally locking material. In this paper, the speed of propagation for the shock waves is analyzed, and results are given. The Mie-Gruneisen equation of state is used to find the pressure as a function of the density. Results with the present model yield an efficient and comprehensive means to analyze speed of waves in a sandy medium.